Simplex approaches to develop reading competence in primary school - Di Tore, Stefano; Zollo, Iolanda; Todino, Michele D.; Sibilio, Maurizio (Education Sciences & Society - Open Access, 2016)
Survey results from IEA PIRLS (2011),OECD PISA (2012) and by further research conducted by the University of Salerno, have shown that the reading performance of Southern Italian students is below the national average. This worrying scenario led to a research initiative aimed at creating inclusive didactic methods and tools to aid in the development of reading competence on the basis of simplex didactics. This theoretical framework sustains our assumption that reading is an ability that does not form part of the natural development of the individual but needs to be learnt; hence is considered as an adaptive strategy (Berthoz, 2012). Therefore, simplex didactics, understood as a method based on the principles that guide the organisms’ adaptation to the surrounding environment, was a natural choice. The research project is divided into four main phases: a preliminary phase, a design phase, field research, followed by the analysis and evaluation of results. It is important to highlight that the scope of this article is to present the initial phase of the research and is intended to: 1. provide an analysis of the context to assess the effective need to introduce a teaching method able to face the critical situation described; 2. explore possible mapping between reading competence and simplex didactics to provide teachers with initial didactic guidelines; 3. introduce the research perspectives upon which the project will be developed. Keywords Reading competence; Didactics; Inclusion; Simplexity; Teacher education